HilbertCurve: an R/Bioconductor package for high-resolution visualization of genomic data - Gu, Zuguang; Eils, Roland; Schlesner, Matthias (Bioinformatics, 2016)
Abstract. Summary: Hilbert curves enable high-resolution visualization of genomic data on a chromosome- or genome-wide scale. Here we present the HilbertCurve